PENGARUH TINGKAT PEMAHAMAN DAN KESADARAN MUZAKKI DALAM MEMBAYAR ZAKAT (STUDI KASUS UNIVERSITAS PELITA BANGSA) - Ahmad, Ali Nur; Susanto, Hadi (DPPM Universitas Pelita Bangsa, 2021)
This study aims to determine Muzakki's level of understanding and awareness in paying zakat. find out the potential of zakat in the Pelita Bangsa academic community, because based on the author's field observations, the author suspects that the Pelita Bangsa academic community consists of lecturers, employees, and students who earn quite a lot. In this study, using the type of field research (field research) with a quantitative approach through distributing questionnaires and questionnaires that have been distributed directly to respondents. Research on the level of understanding and awareness of muzakki in paying zakat. The population used in this study is the academic community consisting of lecturers, students, and employees, who play a role in the implementation of zakat in Pelita Bangsa University. The population that will be the object of research is 100 respondents. Based on the results of research data analysis and calculations that have been carried out by researchers, it can be concluded that there is a significant influence between the level of understanding on muzakki paying zakat. With a coefficient value of 0.727 when compared with the value of rtable at a significant level of 5% of 0.197 then rcount > rtable (0.727> 0.197) so that the coefficient value is significant, there is also a significant influence between the level of awareness of muzakki paying zakat. With a coefficient value of 0.657 when compared with the value of rtable at a significant level of 5% of 0.197, then rcount > rtable (0.657> 0.197) so that the coefficient value is significant, and the results of the analysis conducted by researchers obtained a value of fcount of 54.952. When compared with the value of the fable with a significance level of 5% of 3.09. Then fcount > ftable (54,952> 3.09) so that this value can be said to be significant. This means that the level of understanding and awareness simultaneously influences muzakki to pay zakat.